A Sociopragmatic Study of Insinuation in "The Daily Show - Hawraa Jabbar Rahi (مجلة الباحث, 2025)
This study explores the sociopragmatics of insinuation in the context of "The Daily Show". Drawing from speech act theory and various pragmatic strategies, this study examines how insinuation is activated in the context of "The Daily Show" by making critiques of political figures, media narratives, and societal issues. Insinuation is particularly selected for the reason that it has not been given a deep analysis by researchers from a sociopragmatic perspective, as much as the researcher could investigate. Consequently, this knowledge gap needs to be bridged by socipragmatically examining insinuation in the context of "The Daily Show". This study, therefore, is an attempt to achieve the following aims: identifying the sociopragmatic criteria that indicate the activation of insinuation; pinpointing the pragmatic strategies used to reflect insinuation in the context of "The Daily Show"; and showing how insinuation in "The Daily Show" is shaped by social factors which influence how utterances are constructed, interpreted